Notational comparison analysis of outdoor badminton men`s single and double matches - Perez-Turpin, J. A.; Elvira-Aranda, C.; Cabello-Manrique, D.; Gomis-Gomis, M. J.; Suarez-Llorca, C.; Andreu-Cabrera, E. (Journal of Human Kinetics, 2020)
The objectives of this study were to determine the results of the analysis of single and double outdoor badminton men`s matches and to determine the relationship between technical and tactical aspects in a study organized by the BWF (Badminton Word Federation), on a sand surface. Twenty men`s singles matches were recorded using video cameras and analysed with a Dartfish video analysis software package. Along with this, percentages of use of technical elements were analysed by comparing the different modalities. For the single format Lob, Clear, Drop, Smash, Drive were used, different from the double format that used Lob, Clear, Drop, Smash, Drive. The study confirmed the applicability of computerized notation analysis to determine the characteristics of Outdoor Badminton on sand.